Impact of manganese on primary hippocampal neurons from rodents - Daoust, Alexia (2014)
Manganese-enhanced magnetic resonance imaging (MEMRI) is a powerful tool for in vivo tract tracing or functional imaging of the central nervous system. However Mn2+ may be toxic at high levels. In this study, we addressed the impact of Mn2+ on mouse hippocampal neurons (HN) and neuron-like N2a cells in culture, using several approaches. Both HN and N2a cells not exposed to exogenous MnCl2 were shown by synchrotron X-ray fluorescence to contain 5 mg/g Mn. Concentrations of Mn2+ leading to 50% lethality (LC50) after 24 h of incubation were much higher for N2a cells (863 mM) than for HN (90 mM). The distribution of Mn2+ in both cell types exposed to Mn2+ concentrations below LC50 was perinuclear whereas that in cells exposed to concentrations above LC50 was more diffuse, suggesting an overloading of cell storage/detoxification capacity. In addition, Mn2+ had a cell-type and dose-dependent impact on the total amount of intracellular P, Ca, Fe and Zn measured by synchrotron X-ray fluorescence. For HN neurons, immunofluorescence studies revealed that concentrations of Mn2+ below LC50 shortened neuritic length and decreased mitochondria velocity after 24 h of incubation. Similar concentrations of Mn2+ also facilitated the opening of the mitochondrial permeability transition pore in isolated mitochondria from rat brains. The sensitivity of primary HN to Mn2+ demonstrated here supports their use as a relevant model to study Mn2+-induced neurotoxicity.